2019
DOI: 10.1021/acsami.9b14487
|View full text |Cite|
|
Sign up to set email alerts
|

Aptamer-Based Fluorescent Biosensing of Adenosine Triphosphate and Cytochrome c via Aggregation-Induced Emission Enhancement on Novel Label-Free DNA-Capped Silver Nanoclusters/Graphene Oxide Nanohybrids

Abstract: Four fluorescent DNA-stabilized fluorescent silver nanoclusters (DNA–AgNCs) were designed and synthesized with differences in lengths of cytosine-rich DNA strand (as the stabilizing agent) and target-specific strand DNA aptamers for adenosine triphosphate (ATP) and cytochrome c (Cyt c). After their nanohybrid formation with graphene oxide (GO), it was unexpectedly found that, depending on the composition of the base and length of the strand DNA aptamer, the fluorescence intensity of three of the nanohybrids si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
0
45
0
1
Order By: Relevance
“…Besides thiolate‐protected MNCs, DNA‐Ag NCs have recently been shown to have AIE activity. [89] It was found that DNA‐Ag NCs have enhanced emission after being immobilized on the surface of GO. Based on this observation, DNA‐Ag NCs/GO hybrid was fabricated for label‐free detection of ATP and cytochrome c (Figure 6D).…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…Besides thiolate‐protected MNCs, DNA‐Ag NCs have recently been shown to have AIE activity. [89] It was found that DNA‐Ag NCs have enhanced emission after being immobilized on the surface of GO. Based on this observation, DNA‐Ag NCs/GO hybrid was fabricated for label‐free detection of ATP and cytochrome c (Figure 6D).…”
Section: Biosensing Strategiesmentioning
confidence: 99%
“…Recently, Shamsipur et al (2019) reported a new AIE-active luminescent sensor based on DNA-AgNCs/GO (graphene oxide) nanohybrids for the detection of triphosphate (ATP) and cytochrome (Cyt) c in cell lysates. The working principle is shown in Figure 2 .…”
Section: Ultrasmall Au and Ag Ncs For Biomedical Applicationsmentioning
confidence: 99%
“…In the absence of a target, the DNA-AgNCs are adsorbed onto the GO surface, while the fluorescence is enhanced because of the AIE enhancement characteristic of DNA-AgNCs when they are adsorbed onto the GO surface. Upon target binding, the conformation of specific aptamers is significantly altered and AgNCs are desorbed on the GO surface, leading to the restoration of the fluorescence signal ( Shamsipur et al, 2019 ). This study opens a new avenue for designing noble metal NCs-based AIE sensors, where the performance stability of such Ag NCs-based AIE sensors must be further examined in future studies.…”
Section: Ultrasmall Au and Ag Ncs For Biomedical Applicationsmentioning
confidence: 99%
“…Specifically, the impact of nanosilver is thought to be related to the release of silver ions, reactive oxygen production, and the direct interactions with biomacromolecules proteins and nucleic acid ( 6–10 ). Silver nanoclusters (AgNCs) have gained tremendous attention in recent years owing to the significant promises for fundamental research, as well as nanotechnology-based technological and biological applications ( 11 , 12 ). The outstanding physicochemical characteristics of AgNCs, including low cost, excellent dispersibility, easy preparation, facile functionalization, tunable emission wavelength, and high catalytical activity ( 13–16 ), have boosted their multidisciplinary applications in areas of catalysis ( 17 , 18 ), biosensing and disease diagnosis ( 19–21 ), biological imaging ( 22 , 23 ), biomedicine ( 24 , 25 ), antimicrobial agent ( 26 ), optoelectronics ( 27 ), and complex logic gates/logic device fabrications ( 13 , 28 ).…”
Section: Introductionmentioning
confidence: 99%